Meropenem Administered via Intravenous Regional Limb Perfusion for Orthopedic Sepsis in Horses: A Clinical Retrospective Study - Mosichuk, Allison P.; Smith, Joseph S.; Tatarniuk, Dane M.; Troy, Jarrod R.; Kreuder, Amanda J. (Frontiers in Veterinary Science, 2021)
Septic synovitis is a critical orthopedic condition in horses. Early intervention is key, with antibiotic therapy typically initiated prior to culture and susceptibility reports becoming available. The pharmacokinetics of several antibiotics have been studied in horses for use in intravenous regional limb perfusion (IVRLP) for septic synovitis, including the carbapenem antibiotic, meropenem. For a variety of factors, some veterinary clinicians may select IVRLP meropenem as therapy for these cases. Meropenem is a vital antibiotic in human medicine, making veterinary use divisive. However, verifying the efficacy of meropenem contrasted to other IVRLP antibiotics is essential for appropriate antimicrobial stewardship. To investigate this, equine patient medical records at a single veterinary teaching hospital were examined. Cases treated with meropenem or gentamicin via IVRLP for septic synovitis were retrospectively analyzed for demographics, diagnostics, treatments, outcomes, and adverse effects. Twenty-three meropenem and 37 gentamicin treated horses were analyzed; demographic information was similar between groups. In the meropenem group, nine horses received meropenem only; the remainder received another antibiotic initially then changed to meropenem. Structures infected included joints (meropenem = 13, gentamicin = 17), tendon sheaths (meropenem = 5, gentamicin = 8) and navicular bursae (meropenem = 2, gentamicin = 6). Overall survival to discharge was 86% (52/60), with meropenem 91% (21/23) and gentamicin 84% (31/37), with no statistically significant differences noted between meropenem or gentamicin groups for overall survival to discharge or outcome after discharge. Twenty-four of 26 bacterial isolates obtained from culture were reported as sensitive to imipenem, a carbapenem antibiotic similar to meropenem. Reported susceptibility to other antibiotics such as ceftiofur (n = 22/26), ampicillin (n = 18/26), amikacin (n = 15/26), or gentamicin (n = 12/26) was also frequently present. In the population of this study, antimicrobial activity augmented with IVRLP using either meropenem or gentamicin both appear to be an effective treatment for septic synovial structures, therefore, less critical antimicrobials may be a viable and more judicious treatment option.